Roman amphora contents : reflecting on the maritime trade of foodstuffs in antiquity : in honour of Migeul Beltrán Lloris : proceedings of the Roman Amphora Contents International International Conference (RACIIC) (RACIIC) (Cádiz, 5-7 October 2015) - Beltrán Lloris, Miguel,; Bernal-Casasola, Darío,; Bonifay, Michel, 1957-; Pecci, Alessandra,; Leitch, Victoria, (Roman and late antique Mediterranean pottery ;, 2021)
Presents the results of the RACIIC International Congress (Roman Amphora Contents International Interactive Conference, Cádiz, 2015), dedicated to the distinguished Spanish amphorologist Miguel Beltrán Lloris. This volume aims to reflect on the current state of knowledge about the palaeocontents of Roman amphorae.